PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING DAN MOTIVASI BELAJAR FISIKA TERHADAP KEMAMPUAN PEMECAHAN MASALAH PESERTA DIDIK DI SMA NEGERI 3 TAKALAR - Jumriati Jumriati; Sidin Ali; Khaeruddin Khaeruddin (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2020)
Research has conducted which aims to find out: (1) how big is the problem-solving ability of students who taught through discovery learning model learning with students who taught through conventional models of State 3 Takalar dimSMA (2) as a whole, whether there are differences in the ability to solve physics problems between students taught with discovery learning and conventional learning models in SMA Negeri 3 Takalar (3) as a whole, is there a difference in the ability to solve physics problems for students who have high learning motivation and students who have low learning motivation in SMA Negeri 3 Takalar (4) whether there is an interaction between learning models with learning motivation towards students' physics problem-solving abilities at SMA Negeri 3 Takalar. This research is an experimental research using a 2x2 factorial design. Hypothesis testing performed at a significance level of 5% or α = 0.05. The results showed that: (1) The problem-solving ability of students taught through discovery learning models had higher average scores compared to students taught through conventional models at SMA Negeri 3 Takalar (2) Overall, where differences in ability physics problem solving between students taught with discovery learning and traditional learning models in SMA Negeri 3 Takalar (3) Overall, there are differences in the ability to solve physics problems for students who have high learning motivation and students who have low learning motivation in high school Negeri 3 Takalar (4) There is no interaction between the learning model and the motivation to learn physics to the students' physics problem-solving abilities at SMA Negeri 3 Takalar.